Assistive technologies : principles & practice - Cook, Albert M., ....-; Polgar, Janice M., ....-; Encarnação, Pedro, ....- (Missouri (Mo.) : Elsevier, 2020)
Master the assistive strategies you need to make confident clinical decisions and help improve the quality of life for people with disabilities. Based on the Human Activity Assistive Technology (HAAT) model developed by Al Cook, Sue Hussey and Jan Polgar, Assistive Technologies: Principles & Practice, 5th Edition, provides detailed coverage of the broad range of devices, services, and practices that comprise assistive technology. This new text offers a systematic process for ensuring the effective application of assistive technologies - and focuses on the relationship between the human user and the assisted activity within specific contexts. It features over 30 new photos and illustrations, as well as, updated chapters and case studies that reflect current technology. Key Features Human Activity Assistive Technology (HAAT) framework locates assistive technology within common, everyday contexts for more relevant application. Focus on clinical application guides application of concepts to real-world situations. Study questions and chapter summaries in each chapter help assessment of understanding and identification of areas where more study is needed. Coverage of changing AT needs throughout the lifespan emphasizes how AT fits into people's lives and contributes to their full participation in society. Principles and practice of assistive technology provide the foundation for effective reasoning. Ethical issues content provides vital information to guide AT service delivery. Explicit applications of the HAAT model in each of the chapters on specific technologies and more emphasis on the interactions among the elements make content even easier to understand. New to this Edition New! Thoroughly updated chapters to reflect current technology and practice. New! Expanded discussion on assistive robotics and smart technologies. New! Review of global initiatives on Assistive Technology. New! Updated art program with 30+ new photos and illustrations. New! Updated case
Keywords: Assistive technology; Ergotherapie; Occupational therapy